(N{EDEWRY PRIKLADNOGO ISKUSSTWA uZBEKISTANA(B.s (NISKUSSTWO(B. (NaLXBOMs - (NnARGIZA tALIPOWAs ((NtA[KENTs Print media, 2011)
(N|TO KNIGA PRO [EDEWRY PRIKLADNOGO ISKUSSTWA uZBEKISTANA(B.s
Keywords: (NpRIKLADNOE ISKUSSTWAs